Analisis Hadis tentang Ekoteologi dan Relevansinya dalam Membangun Kesadaran Lingkungan melalui Pendidikan Sekolah Alam - Lutfiyah, Siti Khumairotul; Kurjum, Mohamad (JURNAL PENDIDIKAN ISLAM AL I’TIBAR, 2024)
Islam as the majority religion in Indonesia has teachings that pay great attention to the balance between humans and nature. Hadith of ecotheology and nature school education complement each other in an effort to increase environmental awareness. The type of research used is qualitative with library research, by collecting library sources, both primary and secondary. Islamic teachings on the environment can be found in the Qur'an and hadith. In data processing, the first step taken by the researcher is to take a takhrij of the cited hadith to show the source of the hadith in question. The results of this study are: 1) Hadiths related to the environment or hadith of ecotheology contain noble values about the importance of preserving nature. 2) Hadith of ecotheology provides a strong moral and spiritual foundation, while natural school education provides space for students to implement these values in daily life. 3) The collaboration between the two can give birth to a young generation who have a high concern for the environment and are committed to preserving nature for future generations.